2016
DOI: 10.18488/journal.1/2016.6.2/1.2.93.107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Drivers and Agents of Deforestation and Forest Degradation in Masito Forests, Kigoma, Tanzania

Abstract: A study to assess the direct and indirect drivers and agents of deforestation and forest degradation was carried out in Masito forests in Kigoma Region. Several methodologies were deployed including review of key literature, focused group discussions, household level interviews and review of "smart phones" database of disturbance incidences in the forests. Results revealed that despite forest protection measures taken by the government and other actors for purposes of REDD+ carbon trade, deforestation and fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 1 publication
3
16
0
Order By: Relevance
“…However, the chisquare test shows no significance difference in the responses from households regarding the effect of forest fire. This finding corroborate those of Kessy et al (2016) and Mohammed et al (2013) who observed that humaninduced forest fire was the major causes of forest degradation in REDD+ project villages in Tanzania and National Parks in Nigeria. Majority (86%) of the respondents indicated that poor grazing management in the reserve pose serious conservation threats to forest resources in the area.…”
Section: Drivers Of Forest Resource Degradation As Perceived By the Csupporting
confidence: 91%
“…However, the chisquare test shows no significance difference in the responses from households regarding the effect of forest fire. This finding corroborate those of Kessy et al (2016) and Mohammed et al (2013) who observed that humaninduced forest fire was the major causes of forest degradation in REDD+ project villages in Tanzania and National Parks in Nigeria. Majority (86%) of the respondents indicated that poor grazing management in the reserve pose serious conservation threats to forest resources in the area.…”
Section: Drivers Of Forest Resource Degradation As Perceived By the Csupporting
confidence: 91%
“…Since drivers of AGC removals are similar to drivers for forest degradation in the woodlands meant for both protective and production purposes, comparison across studies were based on studies conducted to determine forest degradation drivers. The result found in the present study is comparable to results found in miombo woodland in Masito forest in western Tanzania and Liwale district southern Tanzania[23,24,25].These studies documented only six drivers responsible for forest degradation. Sites specific and the methodologies applied on these studies explains fewer documentation of drivers.…”
supporting
confidence: 86%
“…Increasing population growth and consequent increase in settlement and farmlands may have extirpated important fauna and flora in the Ulugurus (Bjørndalen 1992, Burgess et al 2002, Burgess et al 2001, Burgess et al 2007, Hall 2009, Yanda and Shishira 1999) - Figure 5. Habitat fragmentation in the study area can also be attributed to a complex nexus of socioeconomic processes (Kessy et al 2016, Rosales 2008. These processes act at various scales i.e.…”
Section: Drivers To Habitat Fragmentation and Conservation Implicationsmentioning
confidence: 99%
“…international (global forest products market growth, commercialization and urbanization), national (changing population, growing local markets and national legislation and governance) and local conditions (livelihoods and levels of poverty) (Wehkamp et al 2015, FAO 2007, Daly and Farley 2004, Czech 2013. Kessy et al (2016) for instance notes that local and international demand for timber and agricultural commodities in a globalizing world are major drivers to forest fragmentation in the area. Globalization, with its characteristic scramble by the developing countries to increase their market share on the global marketplace has increased pressure on existing forests and forest land (Hecht andSaatchi 2007, Rosales 2008).…”
Section: Drivers To Habitat Fragmentation and Conservation Implicationsmentioning
confidence: 99%